Strategi Manajemen Pendidikan dalam Mengintegrasikan Nilai-Nilai Pancasila di Madrasah - Iswiyanto, Hendra Ani (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to describe the educational management strategy for integrating Pancasila values ​​into the school environment and identify factors that support and inhibit the integration process. Using a descriptive qualitative approach, this study was conducted at MA. Raadhiyatan Mardhiyyah Putra Balikpapan has informants consisting of the principal, PPKn teachers, homeroom teachers, and students. Data were collected through observation, interviews, and documentation, and analyzed using the Miles & Huberman data analysis model. The study results indicate that the integration of Pancasila values ​​is carried out through curriculum planning, habituation of positive activities, strengthening school culture, and collaboration between stakeholders. Principal management is a key factor in implementing a Pancasila-based character education program. These findings strengthen the theory that effective educational management plays an important role in shaping student character, with an integrative curriculum, strengthening school culture, and close collaboration between schools and parents. However, challenges such as lack of teacher understanding of the integrative approach, high administrative burden, and minimal technical guidance can hinder the effectiveness of implementation. The implications of this research show that structured educational management plays a strategic role in internalizing national values ​​in students